Pan Magic - Chen, Willi (TandT Review)
A short story by Willi Chen entitled "Pan Magic" which tells the tale of Milton Lyons, a poor handy man- pan beater from Marabella who wanted to compete in the solo tenor pan category at the Carnival celebrations.
Keywords: Steel band music -- Trinidad and Tobago; Short stories, Trinidadian and Tobagonian (English) -- Fiction; Steel bands (Music) -- Trinidad and Tobago